Beyond Self‐Reports: Changes in Biomarkers as Predictors of Mortality. Issue 2 (June 2014) - Glei, Dana A.; Goldman, Noreen; Rodríguez, Germán; Weinstein, Maxine
<x xml:space="preserve">Abstract</x> The proliferation of biosocial surveys has increased the importance of weighing the costs and benefits of adding biomarker collection to population‐based surveys. A crucial question is whether biomarkers offer incremental value beyond self‐reported measures, which are easier to collect and impose less respondent burden. We use longitudinal data from a nationally representative sample of older Taiwanese (aged 54+ in 2000, examined in 2000 and 2006 with mortality follow‐up through 2011) to address that question with respect to predicting all‐cause mortality. A summary measure of biomarkers improves mortality prediction (as measured by the area under the receiver operating characteristic curve) compared with self‐reports alone, but individual biomarkers perform better than the summary score. We find that incorporating change in biomarkers over a six‐year period yields a small improvement in mortality prediction compared with one‐time measurement. But, is the incremental value worth the costs?